Learning to Live with Cheaper Oil : Policy Adjustment in MENA and CCA Oil-Exporting Countries - Sommer, Martin; Auclair, Allan; Fouejieu, Armand; Lukonga, Inutu (Washington, D.C. : International Monetary Fund, 2016)
This paper discusses the challenges posed by low oil prices in the MENA and CCA regions, the adjustment policies adopted so far, and remaining adjustment needs and future risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet